Software Project Management for Dummies - Luckey, Teresa, Phillips, Joseph (Wiley, 2006)
This book was written in a formatthat coincides with the natural progression of a software project, from planning stages until the very end. This book contains six majors parts, and each part contains several chapter that might have relevant information for some project.